Police reform, austerity and ‘cop culture’: time to change the record? - Caveney, Nick (Policing and society, 2020)
Austerity, a politicised police reform agenda and increasing demand for police services create the collective conditions that require classical views of police culture be seen through a fresh contextual lens. Triangulating participant observation, semi-structured interviews and archival and documentary review within two UK police forces, we identify dramatic organisational and environmental changes across the UK policing landscape as the prime factors reconceptualising traditional views of police cultural theory. We argue for a context-specific, more pluralistic understanding, highlighting the importance within current police culture of public service motivation and the role of public servant, reduced intra-group solidarity and concepts of victim categorisation differing from previous typologies. Some facets of traditional concepts of police culture, such as residual racism, are resilient; other aspects, such as the role of autonomy and the meaning ascribed to getting a ‘result’, are now better understood in novel ways.